More-Than-Human Aesthetics: Lessons from Enrichment - Alinta Krauth (Pulse)
This interdisciplinary research investigates the potentials of animal enrichment as it pertains to the conceptualisation of more-than-human aesthetics. This occurs by analysing the creation of a series of digitally interactive sculptures called the Quantum Enrichment Entanglers (2021-2022), designed with and for flying foxes in rehabilitation care. In doing so, I argue for a multispecies future for arts practices in which the human perceiver is decentred, and the needs, wants, and practices of other species are considered within the interactive arts. While we cannot yet know the phenomenal experiences of other species, I contend that through knowledges from the fields of animal enrichment design, we are 1 better able to create cultural artefacts and artistic outcomes that cultivate joy or interest beyond our own species. This research is situated within a practice-based research approach, informed by animal enrichment design. I develop processes of approaching animal participants with interactive stimuli in order to reflect on engagements between animals and artefacts. This develops its own aesthetic register based on what I call sensory affordances.